Occupational palmoplantar psoriasis: a clinical case series with consideration of the S1 guidelines on expert medical assessments of occupational psoriasis - Angelovska, Irena; Mahler, Vera (Journal der Deutschen Dermatologischen Gesellschaft, 2014)
Constitutional diseases represent a challenge in the expert assessment of occupational diseases. It is necessary to distinguish professional causes from the spontaneous course of the disease. Recently, a guideline for the assessment of work-related psoriasis has been consented in Germany. We present a case series in which it was applied.129 expert assessments from the Department of dermatology University hospital Erlangen and court cases in established juridical databases were researched for cases with psoriasis and the applicability of the guideline.The guideline was applicable in the n = 6 (3.6 %) identified medical expert opinions. They were fully recognized by the workers compensation boards. The search for law sentences on work-related psoriasis in German court cases yielded a total of four sentences, in one of which the psoriasis was recognized as an occupational disease (BK 5101).In comparison with hand eczema psoriasis of the hands is rare. As has been demonstrated in our case series psoriasis as a constitutional disease may be recognized as an occupational disease (BK 5101) according to the legal system in Germany, if the influence of occupational exposure can be made sufficiently probable and other legal conditions of an occupational disease are met.
EVALuna2:19456